Analysis of Investment Potential in The West Part of Jambi Province - Muhammad Safri (Universitas Batanghari Jambi, 2023)
This study aims to provide accurate information about business fields, commodities and potential in Jambi Province to investors (investors). Therefore this research is needed so that the level of development in Jambi Province is right on target. The scope of this research area covers all locations of Sarolangun Regency, Merangin Regency, Bungo Regency, Tebo Regency, Kerinci Regency and Sungai Penuh City. The type of data used is the type of secondary data obtained from interviews and data from related agencies in the Province of Jambi in 2017. Based on the research results obtained that: (1) Jambi Province is one of the provinces geogrogically has a very strategic location. supported by land and sea and air transportation facilities and infrastructure including the Trans Sumatra national road and so on. Jambi Province is included in the IMT-GT growth triangle Economic Zone (KESR). (2) The results of the SWOT analysis that have been carried out show the potential investment results in Jambi Province are in Quadrant III (negative, positive) between strategic issues on internal factors of weakness and opportunity external factors, which in this position indicates that in terms of investment the Province of Jambi has several weaknesses but has great opportunities for investment development in Jambi Province. (3) Based on the results of the 2018 Klassen Typology analysis of 6 (six) regencies/cities that are the study areas, including Merangin Regency, Sarolangun Regency, Bungo Regency, Tebo Regency, Sungai Penuh and Kerinci District showing that only Sungai Penuh City is included the classification of Fast-Forward and Fast-Growing Regions, with a rate of economic growth and per capita income higher than the provinces. For regions that are classified as fast developing regions are Sarolangun Regency, Bungo Regency, Tebo Regency, Merangin Regency and Kerinci Regency. Although it has a lower per capita income than the provincial per capita income, the economic growth rates of the five districts are higher than the provincial economic growth rate. The area is an area that can develop rapidly with very large development potentials but has not been fully processed properly